2022
DOI: 10.1111/ctr.14631
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal antimicrobial prophylaxis to prevent postoperative infectious complications after liver transplantation? A systematic review of the literature and expert panel recommendations

Abstract: Background Antimicrobial prophylaxis is well‐accepted in the liver transplant (LT) setting. Nevertheless, optimal regimens to prevent bacterial, viral, and fungal infections are not defined. Objectives To identify the optimal antimicrobial prophylaxis to prevent post‐LT bacterial, fungal, and cytomegalovirus (CMV) infections, to improve short‐term outcomes, and to provide international expert panel recommendations. Data sources Ovid MEDLINE, Embase, Scopus, Google Scholar, and Cochrane Central. Methods Systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…Regarding liver transplantation, the incidence of PJP is around 7% of all cases of pneumonia, with mortality ranging from 7% to 88% [ 63 ]. However, the overall incidence of PJ infection has fallen in recent years due to fewer immunosuppressive regimens used after LT, and according to recent data, the incidence in recipients that undergo prophylaxis is below 2% and <1% in the first year after LT. Contrarily, the incidence rises to 11% in patients without prophylaxis [ 63 , 64 ]. Considerations for PJP prophylaxis include the degree of immunosuppression preceding LT, the duration and form of post-LT immunosuppression, the absolute lymphocyte count, and the presence of a concurrent solid organ transplant.…”
Section: Fungal Infection: Pneumocystis Jiroveciimentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding liver transplantation, the incidence of PJP is around 7% of all cases of pneumonia, with mortality ranging from 7% to 88% [ 63 ]. However, the overall incidence of PJ infection has fallen in recent years due to fewer immunosuppressive regimens used after LT, and according to recent data, the incidence in recipients that undergo prophylaxis is below 2% and <1% in the first year after LT. Contrarily, the incidence rises to 11% in patients without prophylaxis [ 63 , 64 ]. Considerations for PJP prophylaxis include the degree of immunosuppression preceding LT, the duration and form of post-LT immunosuppression, the absolute lymphocyte count, and the presence of a concurrent solid organ transplant.…”
Section: Fungal Infection: Pneumocystis Jiroveciimentioning
confidence: 99%
“…Considerations for PJP prophylaxis include the degree of immunosuppression preceding LT, the duration and form of post-LT immunosuppression, the absolute lymphocyte count, and the presence of a concurrent solid organ transplant. In addition, in this patient cohort, prophylaxis should be explored for patients undergoing therapy for acute rejection events [ 63 , 64 ]. Most cases of PJP occurred in the first 7 months after LT [ 63 ], although Fortea et al, in their survey, recently showed a not insignificant number of PJ infections occurring beyond the usually recommended period of prophylaxis [ 65 ].…”
Section: Fungal Infection: Pneumocystis Jiroveciimentioning
confidence: 99%
See 2 more Smart Citations
“…The present study also revealed that only exposure to more than two post-LT intravenous antibiotics was negatively associated with the acquisition of E 2 SKAPE infections. Despite the proven bene t of antimicrobial prophylaxis in LT programs worldwide, an optimal intervention has never been established [27]. Therefore, at the time of selecting antibiotics, it is necessary to consider individual patient characteristics, local ora and resistance patterns, culture of the preservation uid, and blood cultures obtained from the donor.…”
Section: Analysis Of Risk Factors For In Lt Recipientsmentioning
confidence: 99%